2018
DOI: 10.1016/j.ijsu.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Timing of surgical site infection and pulmonary complications after laparotomy

Abstract: A high percentage of patients undergoing laparotomy develop a postoperative complication. This study adds new knowledge by identifying time intervals within which medical professionals should be aware of surgical site infections and pulmonary complications in order to initiate appropriate treatment of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Recent studies have observed a higher risk of mortality and in-hospital complications among severely obese and morbidly obese trauma patients [25,26], suggesting outcomes in trauma may vary depending on the degree of obesity. While there have been multiple studies on general surgical populations purporting the increased risk for postoperative pulmonary complications (PPCs) and mortality with a laparotomy as well as with obesity independently [16,[27][28][29], fewer studies have specifically examined the association of obese trauma patients requiring trauma laparotomy. Furthermore, obesity is not currently considered among the patient-related risk factors for the development of PPCs [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have observed a higher risk of mortality and in-hospital complications among severely obese and morbidly obese trauma patients [25,26], suggesting outcomes in trauma may vary depending on the degree of obesity. While there have been multiple studies on general surgical populations purporting the increased risk for postoperative pulmonary complications (PPCs) and mortality with a laparotomy as well as with obesity independently [16,[27][28][29], fewer studies have specifically examined the association of obese trauma patients requiring trauma laparotomy. Furthermore, obesity is not currently considered among the patient-related risk factors for the development of PPCs [30].…”
Section: Introductionmentioning
confidence: 99%
“…The overall rate of IC in our population (33.8%) aligns with a recent study by Gundel et al , who identified at least one infectious or respiratory complication in 24% of laparotomy patients. 5 It is understandable that our rate would be somewhat higher because our study population included DCL patients and excluded patients who had primary closure; that is, our study population included more severe, ‘sicker’ patients. The differences in rates of infections and re-explorations were consistent with recent literature as well.…”
Section: Discussionmentioning
confidence: 97%
“…The following patient characteristics were analyzed for association with the exposure and primary variables: age, sex, race, ethnicity, insurance used, injury type (blunt vs. all others), interhospital transfer status, multiple comorbidities and pre-existing conditions, Injury Severity Score (ISS, <16 vs. ≥16), Glasgow Coma Scale score (GCS, 13-15 vs. [3][4][5][6][7][8][9][10][11][12], abnormal emergency department (ED) vital sign measures (oxygen saturation <95%, body temperature <36.4°C or >37.6°C, heart rate <60 or >100 beats per minute, systolic blood pressure (SBP) <90 mm Hg, respiratory rate <12 or >16 breaths per minute).…”
Section: Study Variablesmentioning
confidence: 99%
“…Surgical site infections (SSI), the most common complications after abdominal surgery, are often observed in clinical practice, varying from 4% to 40% ( 1 , 2 ). In the emergency setting, SSI contributes to a more significant proportion of postoperative morbidity, with reported rates of 25% to 40% ( 3 , 4 ). SSI prolongs the hospital length of stay (LOS) and increases the readmission rate and healthcare costs ( 5 ).…”
Section: Introductionmentioning
confidence: 99%